Laboulbeniales (Ascomycota) from Bulgaria and other countries. (2nd January 2019) - Rossi, W.; Guéorguiev, B.; Georgiev, G.; Stoianova, D.
Abstract: Fifty-two species of the Laboulbeniales are reported for the first time from Bulgaria. One new species of Diphymyces, parasitic on Hexaurus schipkaensis is also described. The total number of species from Bulgaria is thus raised from 15 to 68. The first records of any of the Laboulbeniales are reported from Armenia, Eritrea, Georgia and Kazakhstan; more new records are reported also from Albania, China, Cyprus, Hungary, Italy, Mongolia, Namibia, Romania, Slovenia, Switzerland, United Kingdom and Yemen. The antheridia of Misgomyces dyschirii are described and illustrated.